Using the multiple capitals framework to connect indicators of regional cumulative impacts of mining and pastoralism in the Murray Darling Basin, Australia - Moran, Chris; Franks, D.; Sonter, L. (Pergamon Press, 2013)
It is commonly recognized that there are constraints to successful regional-scale assessment and monitoring of cumulative impacts because of challenges in the selection of coherent and measurable indicators of the effects. It has also been sensibly declared that the connections between components in a region are as important as the state of the elements themselves. These have previously been termed "linked" cumulative impacts/effects. These connections can be difficult to discern because of a complicated set of interactions and unexpected linkages. In this paper we diagnose that a significant cause of these constraints is the selection of indicators without due regard for their inter-relationships in the formulation of the indicator set. The paper examines whether the common "forms of capital", i.e., natural (renewable and non-renewable), manufactured, social, human and financial capitals, framework is a potential organizing structure. We examine a large region in western NSW Australia where the predominant production systems are mining and grazing for production of wool, beef and lamb. Production in both is driven by consumption of a non-renewable resource, i.e., ore for mining and topsoil for grazing, the latter on the basis that loss rate estimates far exceed soil formation rates. We propose that the challenge of identifying connections of components within and between capital stores can be approached by explicitly separating stores of capital and the flows of capital between stores and between elements within stores, so-called capital fluxes. We attempt to acquire data from public sources for both capital stores and fluxes. The question of whether these data are a sufficient base for regional assessment, with particular reference to connections, is discussed. The well-described challenge of a comparative common currency for stores and fluxes is also discussed. We conclude that the data acquisition is relatively successful for stores and fluxes. A number of linked impacts are identified and discussed. The potential use of money as the common currency for stores and fluxes of capital is considered. The basic proposition is that replacement or preservation costs be used for this. We conclude that the study is sufficiently positive to consider further research in fully-coupled models of capital stores and fluxes. © 2013.